Tingkat Kepuasan Konsumen Pada Toko-Toko Ikan Hias di Kecamatan Cileunyi (Studi Kasus Toko-Toko Ikan Hias di Kecamatan Cileunyi) - Galih Muhammad Hanuky; Asep Agus Handaka Suryana; Ine Maulina; Atikah Nurhayati (Universitas Mataram, 2024)
This research aims to analyze characteristics of consumers and sellers as well as level of consumer satisfaction in ornamental fish shops in Cileunyi District and analyze main variables that greatly influence level of consumer satisfaction. Data collection and processing was carried out in May – June 2024 at Cileunyi District, Bandung Regency. The research method used is case study method, with a sampling technique namely purposive sampling. The analysis used is Customer Satisfaction Index (CSI) and Descriptive Marketing Mix. The results of this research showed that CSI value was 80.5% in satisfied category. The main variables that most influence consumer satisfaction are variables of medicinal and vitamin products for ornamental fish, ornamental fish in healthy condition, traders providing information that is easy for consumers to understand, ornamental fish traders greeting